Principal Conflict Management in Improving Junior High School Teacher Performance - Kamaluddin; Bahrun; Suparta Rasyid; Fitri Setiawati; Syamsul Arifin (LPPM Undiksha, 2026)
The reality within school environments indicates the presence of disciplinary gaps, mismatches in teaching backgrounds, and social disparities among teachers, thereby requiring principals to demonstrate strategic managerial competence in conflict management to foster a harmonious and productive working environment. This study aims to analyze the conflict management strategies employed by principals in improving the performance of junior high school teachers. This research adopted a qualitative design with a descriptive approach. Data were collected through classroom observations, in-depth interviews, and document analysis. The research instruments included observation guidelines, semi-structured interview protocols, and documentation sheets. The informants consisted of the principal, teachers, and administrative staff. Data were analyzed using qualitative descriptive techniques. The findings reveal that improvements in teacher performance are significantly influenced by effective principal leadership implemented through several conflict management strategies. First, coordination of teaching workload distribution was conducted transparently and equitably by accommodating teachers’ aspirations. Second, the consistent application of fairness principles was implemented through objective reward and sanction mechanisms to foster teacher motivation and trust. Third, a problem-solving orientation was cultivated by promoting open communication and teamwork in conflict resolution processes. The study concludes that collaborative, fair, and adaptive conflict management contributes to the creation of a conducive working climate and enhances teacher professionalism and motivation.